Studi Karakteristik dan Sistem Pengolahan Air Limbah Domestik di Kota Kendari - Pratama, Rahmat Juniadi; Rosdiana, Rosdiana; Adami, Aryani (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2025)
Wastewater is water resulting from human activities that contains compounds that are harmful to humans. In addition, waste can also cause irritation, poisoning, genetic mutations, and cancer in humans, especially in Baruga District, Kendari City. Therefore, in the wastewater management process, there needs to be a handler whose goal is to determine whether the waste is hazardous or not, so that appropriate treatment steps can be implemented to overcome any negative impacts that may arise. The process of managing domestic wastewater and waste characteristics needs to be carried out using data analysis techniques that include quantitative and qualitative approaches. Sampling was carried out in one of the water bodies in Kendari City. The sampling procedure refers to SNI 6989.59:2008 concerning sampling procedures. The results of laboratory testing of domestic wastewater samples from Baruga District, Kendari City, Southeast Sulawesi Province found that five of the seven test parameters exceeded the quality standards stipulated in the Regulation of the Minister of Environment No. 68 of 2016, namely TSS (510 mg/L), pH (5.17), COD (128 mg/L), BOD (36.70 mg/L), and Total Coliform (8,200 CFU/100 mL). Meanwhile, the parameters of Ammonia (4.90 mg/L) and Oil & Fat (0.19 mg/L) are still within the permitted limits.